Functional study of DAND5 variant in patients with Congenital Heart Disease and laterality defects - Cristo, F. (2017)
Background: Perturbations on the Left-Right axis establishment lead to laterality defects, with frequently associated Congenital Heart Diseases (CHDs). Indeed, in the last decade, it has been reported that the etiology of isolated cases of CHDs or cases of laterality defects with associated CHDs is linked with variants of genes involved in the Nodal signaling pathway. Methods: With this in mind, we analyzed a cohort of 38 unrelated patients with Congenital Heart Defects that can arise from initial perturbations in the formation of the Left-Right axis and 40 unrelated ethnically matched healthy individuals as a control population. Genomic DNA was extracted from buccal epithelial cells, and variants screening was performed by PCR and direct sequencing. A Nodal-dependent luciferase assay was conducted in order to determine the functional effect of the variant found. Results: In this work, we report two patients with a DAND5 heterozygous non-synonymous variant (c.455G>A) in the functional domain of the DAND5 protein (p.R152H), a master regulator of Nodal signaling. Patient 1 presents left isomerism, ventricular septal defect with overriding aorta and pulmonary atresia, while patient 2 presents ventricular septal defect with overriding aorta, right ventricular hypertrophy and pulmonary atresia (a case of extreme tetralogy of Fallot phenotype). The functional analysis assay showed a significant decrease in the activity of this variant protein when compared to its wild-type counterpart. Conclusion: Altogether, our results provide new insight into the molecular mechanism of the laterality defects and related CHDs, priming for the first time DAND5 as one of multiple candidate determinants for CHDs in humans. © 2017 The Author(s).